The Notion of Underclass - Лидия Моррис (Journal of Economic Sociology, 2010)
The interest to the problem of poverty and deprivation in Russia has grown considerably during the last years. Here is the translation of the most interesting part from the Morris’ book in which all the main approaches to underclass conception are analyzed.  The text is given edited by Maria Dobryakova, master student of MSSES.